Notes to lichen-forming and lichenicolous fungi in Ukraine III (CHORNOMORSKI BOTANICAL JOURNAL, 2023)
Materials and methods: field observations and herbarium collections, microscope technique Nomenclature: Index Fungorum Results: In this contribution, new data concerning lichen-forming and lichenicolous fungi in Ukraine are presented. It includes new record, exclusions, and confirmations to the Ukrainian administrative regions of 64 species of lichen-forming and 20 species of lichenicolous fungi in the 57 genera of Acarospora, Agonimia, Arthonia, Bacidia, Botryolepraria, Caloplaca, Candelaria, Ceratobasidium, Circinaria, Clauzadea, Coenogonium, Endococcus, Epithamnolia, Erythricium, Flavoplaca, Illosporiopsis, Intralichen, Ionaspis, Laetisaria, Lathagrium, Lecania, Lendemeriella, Lichenochora, Lichenodiplis, Llimoniella, Parmeliopsis, Peltigera, Petractis, Phaeophyscia, Physcia, Placynthium, Platismatia, Polyblastia, Polychidium, Polyozosia, Porina, Protoparmeliopsis, Pyrenidium, Pyrenochaeta, Pyrenodesmia, Punctelia, Rinodina, Rhizocarpon, Roselliniella, Rusavskia, Scytinium, Spirographa, Stigmidium, Taeniolella, Telogalla, Toninia, Tremella, Trichoconis, Xanthocarpia, Xanthoriicola, Verrucaria. Among them 29 species are the first time reported to the Chernivtsi region, 12 species new to the Sumy region, 10 species new to the Ternopil region, 7 species new to the Ivano-Frankivsk region, 5 species new to the Kyiv and Zhytomyr regions, 4 species new to the Lviv, Cherkasy, Kharkiv, Kherson, Odesa and Volyn regions, 3 species new to the Donetsk region, two species new to the Zakarpattia region, one species new to the Dnipropetrovk, Khmelnytskyi, Kirovograd, Poltava regions as well as one species new to Autonomous Republic of Crimea. The paper includes recent records of lichens and lichenicolous fungi from National Nature Parks of Ukraine: Carpathian, Holosiivsky, Kamianska Sich, Skolivsli Beskydy, Tsumanska Pushcha, Verkhovynsky as well as Carpathian Biosphere Reserve and Cheremosky Regional Landscape Park.
Keywords: biodiversity, new records, Polychidium, Telogalla, Trichoconis.